2016
DOI: 10.1097/aln.0000000000001128
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Mediates Neuroprotection Conferred by Argon in Combination with Hypothermia in Neonatal Hypoxia–Ischemia Brain Injury

Abstract: Background Hypoxic–ischemic encephalopathy is a major cause of mortality and disability in the newborn. The authors investigated the protective effects of argon combined with hypothermia on neonatal rat hypoxic–ischemic brain injury. Methods In in vitro studies, rat cortical neuronal cell cultures were challenged by oxygen and glucose deprivation for 90 min and exposed to 70% Ar or N2 with 5% CO2 balanced with O2, at 33°C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 47 publications
(37 reference statements)
3
53
0
1
Order By: Relevance
“…They concluded that NF-κB, as a potential modulator of apoptosis, may be a downstream target, exerting distinct effects on neuronal cells. These findings were later on supported by Zhao et al [47] in an in vivo model of neonatal hypoxia and brain injury. This argon-mediated suppression of NF-κB and STAT3 signaling was counteracted by TLR inhibition in vitro, rendering these possible pathways.…”
Section: Intracellular Pathways Displaying Argon-mediated Neuroprosupporting
confidence: 53%
See 3 more Smart Citations
“…They concluded that NF-κB, as a potential modulator of apoptosis, may be a downstream target, exerting distinct effects on neuronal cells. These findings were later on supported by Zhao et al [47] in an in vivo model of neonatal hypoxia and brain injury. This argon-mediated suppression of NF-κB and STAT3 signaling was counteracted by TLR inhibition in vitro, rendering these possible pathways.…”
Section: Intracellular Pathways Displaying Argon-mediated Neuroprosupporting
confidence: 53%
“…It is tempting to speculate that HO-1 may be the central and common part in different settings of protection. Zhao et al [47] confirmed the findings with respect to HO-1 in their in vitro OGD and hypothermia model as well as in vivo argon-mediated neuroprotective effects through HO-1 induction. These effects were prominent in both, the cortex and the hippocampal area, while the brain infarct volume was reduced.…”
Section: Intracellular Pathways Displaying Argon-mediated Neuropromentioning
confidence: 64%
See 2 more Smart Citations
“…It has also been demonstrated previously that argon activates protective pathways in the neuronal and cardiac tissue during regional ischaemia. For example, argon increased heme oxygenase 1 expression and Akt phosphorylation in hypoxic neurones . Its effect was found to be blunted by the pharmacological inhibition of phosphoinositide 3‐kinase or extracellular regulated kinase .…”
Section: Discussionmentioning
confidence: 99%